Lessons From the Field: Developing and Implementing an Intervention for Jailed Parents and Their Children. Issue 1 (11th December 2020) - Charles, Pajarita; Kerr, Margaret; Wirth, Jennifer; Jensen, Sarah; Massoglia, Michael; Poehlmann‐Tynan, Julie
Abstract : Objective: In this Lesson from the Field, we describe an intervention designed by our transdisciplinary team focusing on opportunities for enhanced parent–child visits when a parent is incarcerated in jail. We present implementation challenges and lessons learned from our pilot feasibility study. Background: Separation from one's parent because of incarceration has become an increasingly common experience for U.S. children, with one in 14 children experiencing a coresident parent leaving for prison or jail. Parental incarceration is associated with elevated risk for less optimal child development outcomes, yet few evidence‐based interventions are available to mitigate this risk. Experience: Our field experience underscores knowledge about intervention development and lessons learned in four areas: (a) use of visit coaching with jailed parents and caregivers, (b) application of video chat technology, (c) serving families holistically, and (d) developing family‐focused services in jails. Conclusion and Implications: Our study highlights the value of integrating multiple perspectives, ensuring flexibility with families, combining technology with enhanced support strategies, and collaborating with community organizations and government agencies. The intervention can be implemented without extensive training and can be useful across different family professionals working with families involved in the criminal justice system.